Advances in Titration Techniques - Dang Hoang, Vu (IntechOpen, 2017)
In chemistry, titration (a.k.a. titrimetry) is a common laboratory technique used for the determination of the unknown concentration of an analyte. Because of its versatility, the application of various forms of titration can affect nearly all aspects of society. This book is specifically aimed at broadening and deepening the theory and applications of titration. It contains six chapters being organized into three main sections: Volumetric Titration, Isothermal Titration Calorimetry, and Titrimetric Principles in Electrolytic Systems. Each chapter has been well written by internationally renowned experts in the field of chemistry, with mathematical expressions and illustrative examples selectively and logically presented. It is highly recommended for postgraduate students and scientists alike.